Upaya Meningkatkan Kompetensi Guru dengan Memperhatikan Budaya Kerja, Karakteristik Guru Milenial dan Person-Job Fit (Studi Kasus di SD Negeri 16 Meulaboh Kabupaten Aceh Barat) - Syarifuddin, Syarifuddin; Adnan, Muhammad; Karim, Asrul (peusangan, 2024)
This research aims to find research gaps with previous research that describes work culture, characteristics of millennial teachers and person job fit towards efforts to improve teacher competency. The research was conducted on teachers at SD Negeri 16 Meulaboh, West Aceh Regency. Using quantitative descriptive research with an expanatory research approach. To test the hypothesis in this study, regression analysis techniques were used. The results of this research found that efforts to improve teacher competency through work culture, millennial teacher characteristics and personal job fit have the potential to make a positive contribution, both partially and simultaneously. Work culture factors have the biggest influence